Swachh Bharat Abhiyan Clean India Abhiyan - Vishwakarma, Devendra (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
According to the statistics, it has seen that only few percentage of total population have access to the toilets. It is a programmer run by the government to seriously work to fulfill the vision of Father of Nation (Bapu) by calling the people from all walks of life to make it successful globally. Swachh Bharat Abhiyan is a national cleanliness campaign established by the Government of India. This campaign is covering 4041 statutory towns in order to clean roads, streets, and infrastructure of the India. It is a mass movement has run to create a Clean India by 2019. It is a step ahead to the Mahatma Gandhiâs dream of Swachh Bharat for healthy and prosperous life. This mission was launched on 2nd of October 2014 (145th birth anniversary of Bapu) by targeting its completeness in 2019 on 150th birth anniversary of Bapu. The mission has been implemented to cover all the rural and urban areas of the India under the Ministry of Urban Development and the Ministry of Drinking Water and Sanitation accordingly the first cleanliness drive (on 25th of September 2014) of this mission was started by the Indian Prime Minister, Narendra Modi earlier to its launch. This mission has targeted to solve the sanitation problems as well as better waste management all over the India by creating sanitation facilities to all. Swachh Bharat mission is very necessary to run continuously in India until it gets its goal. It is very essential for the people in India to really get the feeling of physical, mental, social and intellectual well-being. It is to make living status advance in India in real means which can be started by bringing all over cleanliness. Below I have mentioned some points proving the urgent need of Swachh Bharat Abhiyan in India.